Treatment of Acute Bacterial Skin and Skin Structure Infection (ABSSSI) with Dalbavancin in Patients with Systemic Inflammatory Response Syndrome (SIRS). (4th October 2017) - Nowak, Michael; Nelson, Jennifer; Rappo, Urania; Chen, Jie; Danelo, Jamie; Gonzalez, Pedro L; LoVecchio, Frank
Abstract: Background: Treating acute bacterial skin and skin structure infections (ABSSSI) in patients with systemic inflammatory response syndrome (SIRS) is challenging. Dalbavancin, a long-acting lipoglycopeptide with potent activity against gram-positive pathogens including methicillin-resistant Staphylococcus aureus (MRSA), is FDA-approved as a single- or 2-dose regimen for ABSSSI. In this subgroup analysis we describe the efficacy and safety of dalbavancin as treatment for ABSSSI in patients with SIRS at baseline. Methods: This was a subanalysis of a previously published randomized, double-blind, phase 3 clinical study in 698 patients with ABSSSI involving deeper soft tissue or requiring significant surgical intervention conducted between April 2014 and March 2015. Patients were randomized (1:1) to receive intravenous dalbavancin in a single (1500 mg) or 2-dose (1000 mg on day 1 and 500 mg on day 8) regimen. Treatment response (≥20% reduction in erythema, with no rescue antibiotic required) was assessed at 48–72 hours; clinical success (resolution or improvement in all signs and symptoms) was assessed at day 14 and day 28. P values were determined using Fisher's exact test for categorical variables and the Wilcoxon rank-sum test for continuous variables. Safety was assessed at every visit. Outcomes for patients meeting SIRS criteria at baseline were compared with those for patients not meeting SIRS criteria. Results: Of the 698 enrolled patients, 303 (43%) of patients met SIRS criteria. Baseline demographics and disease characteristics were similar across groups; patients who met SIRS criteria had a higher median C-reactive protein level, higher rates of cellulitis and were more often treated as inpatients (Figure 1). Dalbavancin efficacy rates were comparable in patients who met and in patients who did not meet SIRS criteria, with clinical success at the final visit (day 28) reported in 91.8% and 92.8% of patients, respectively (Figure 2). The incidence of adverse events was low and similar between both patient groups (Figure 3). Conclusion: Dalbavancin is an effective and well-tolerated treatment for ABSSSI, including in patients who met SIRS criteria. Disclosures: M. Nowak, Allergan plc: Employee, Salary; J. Nelson, Allergan plc: Employee, Salary; U. Rappo, Allergan plc: Employee and Shareholder, Salary; J. Chen, Allergan plc: Employee, Salary; J. Danelo, Allergan plc: Employee, Salary; P. L. Gonzalez, Allergan plc: Employee and Shareholder, Salary; F. LoVecchio, NIH: Grant Investigator, Research grant